2002
DOI: 10.1007/bf02734261
|View full text |Cite
|
Sign up to set email alerts
|

Does singing promote well-being?: An empirical study of professional and amateur singers during a singing lesson

Abstract: This study explored the possible beneficial effects of singing on well-being during a singing lesson. Eight amateur (2m, 6f, age 28-53 yrs) and eight professional (4m, 4f, age 26-49 yrs) singers who had been attending singing lessons for at least six months were included. Continuous ECG was recorded and computerized spectral analysis was performed. Serum concentrations of TNF-alpha, prolactin, cortisol, and oxytocin were measured before and 30 min after the lesson. Five visual analogue scales (VAS, sad-joyful,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
169
3
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(187 citation statements)
references
References 17 publications
6
169
3
9
Order By: Relevance
“…A previous study has shown that oxytocin concentrations increase after taking part in a singing class, although no data were gathered on the degree of social closeness or trust felt between singers in this case (Grape et al 2003). Similarly, the EOS interacts with the dopamine-reward system (Depue and MorroneStrupinsky 2005); opioid antagonists block the subjective 'high' associated with strong dopamine release (Jayaram-Lindstro et al 2004), and previous studies have implicated the reward system in music-induced pleasure (Blood and Zatorre 2001;Koelsch et al 2006;Salimpoor et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…A previous study has shown that oxytocin concentrations increase after taking part in a singing class, although no data were gathered on the degree of social closeness or trust felt between singers in this case (Grape et al 2003). Similarly, the EOS interacts with the dopamine-reward system (Depue and MorroneStrupinsky 2005); opioid antagonists block the subjective 'high' associated with strong dopamine release (Jayaram-Lindstro et al 2004), and previous studies have implicated the reward system in music-induced pleasure (Blood and Zatorre 2001;Koelsch et al 2006;Salimpoor et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…While singing may not immediately leap to mind as a way of addressing this challenge, there is growing evidence that it is one of the more sustainable and accessible cultural activities to assist with integration (Ahlquist, 2006;Cohen et al 2009;Phelan, 2017;Welch et al, 2014). Much of this research focuses on how singing facilitates social bonding (Ford, 2003;Grape et al, 2003;Phelan, 2009, Weinstein et al, 2016. In an evolutionary sense, humans have created and maintained larger social groups than most of their primate relatives and ancestors.…”
Section: Methodol Methodologic Ogica Al C L Consider Onsiderations Atmentioning
confidence: 99%
“…Increases of OT were found in patients after open-heart surgery when they listened to soothing music (Nilsson, 2009). In one study, it is (Grape, 2003) found that OT increased in both amateur and professional singers after 30 minutes of a singing lesson besides increasing joy and attention. Therefore, singing in groups significantly improves individual health and decreases negative effects.…”
Section: Functions Of the Chorusmentioning
confidence: 99%